MODELLING ECONOMICS OF CLOSED-LOOP SUPPLY CHAIN WITH REMANUFACTURING UNDER LIMITED COMPONENT DURABILITY USING LINEAR PROGRAMMING - RAHMANIA, RIZKY ASTARI (2017)
The closed-loop supply chain has gained interest from companies and researchers in the past few years. While some are forced to manage product return due to government’s law and environmental issues, more find closed-loop supply chain to be a new prospect for their business. As the subject grows, it drives companies to be aware of the economic potential of CLSC. Increasing profit by maximising recovery value has become the objective of businesses who are considering to close their supply chain. This study analyzes the profitability of closed-loop supply chain by looking at limited component durability as the technical limitation for remanufacturing. This study also looks at the changes which could occur in the closed-loop supply chain system to investigate the condition in which closed-loop supply chain is no longer profitable. Linear programming is used to model the problem due to its ability to evaluate many possible alternatives. The solution of the problem is obtained using software named LINGO. This study also makes a comparison with similar research regarding durability limit and cost saving. Furthermore, some managerial insights are proposed to give a more operational and applicable interpretation of the problem solution. The result of this study shows that closed-loop supply chain can only be profitable under certain circumstances. The result of this study also indicates that the limited component durability restricts the system.